Abstracts of current studies : The World Bank research program 1996 - World Bank (The World Bank, 1996)
This volume, which contains abstracts of current Bank research projects, reflects the continuing contributions of Bank research. It describes research projects that address governments'policy concerns, meet the practical needs of Bank operational staff, develop research tools methods and construct databases. The volume reports on research projects initiated, under way, or complete in fiscal 1996. The abstracts in the volume describe, for each project, the questions addressed, the analytical methods used, the findings to date, and their policy implications. Each abstract also identifies the expected completion date, the research team, and any reports or publication produced. The abstracts cover 230 research projects and are grouped under nine major headings:poverty and social welfare; environmentally sustainable development; infrastructure and urban development; macroeconomics; international economics; domestic finance; transitional economies; and private sector development and public sector management